Market Integration Analysis of Indonesian Natural Rubber in the World Market - Happy Dewi Purnomowati; Dwidjono Hadi Darwanto; Sri Widodo; Slamet Hartono (Hasanuddin University, 2015)
The integration of the export and import market scan be reflected not only by the relationship between the market price and its imports, but it also can be reflected by the relationship between the market prices of imports and exports. The objective of this study is to analyze the degree of integration of Indonesia’s natural rubber prices in the international market. The data used in this research is secondary time series data in 1980-2013 from IRSG, BPS, FAO, Gapkindo, UN Comtrade, BI, and the World Bank. The method of analysis using the index of Market Connection(IMC) to measure the index of market integration between the price of natural rubber in China, Japan, Singapore, and South Korea as a follower market and the price of natural rubber in the reference market(market leader) in this case is the United States. The results showed that Indonesia’s natural rubber prices in the international market is not integrated with China, Japan, and South Korea for the short term but it may be integrated in the long-term. The result seem to different to the Singapore that it market being integrated with the international market both for short term and long term periods.